Screening for Corynebacterium diphtheriae. Issue 11 (November 1992) - Wilson, A P; Matthews, S; Bahl, M; Efstratiou, A; Cookson, B D
Abstract : A throat swab from a 9 year old girl with pharyngitis yielded a non-toxigenic strain of Corynebacterium diphtheriae var mitis and Streptococcus group G. C pseudodiphtheriticum was isolated from the throats of two of her four brothers. In each case the isolate was sent to the reference laboratory before full identification. The growth was found to be mixed for one brother; the other isolate being a toxin producing C diphtheriae var gravis. The child was asymptomatic and the case proves that all colonial types on the Hoyles plate should be identified.